Distribuição de minerais e genética dos teores de potássio e de cobre em sementes de feijão - Poersch, Nerison Luís (2010)
The common bean (Phaseolus vulgaris L.), besides having high protein food, is also an excellent source of minerals for consuming. However, genetic variability for minerals contents has been observed and the accumulation of minerals occurs differently in the embryo and seed coat of bean seeds. It was not found studies on the genetics levels of potassium and copper in common bean seeds and a little about the potential of genetic improvement to increase in these minerals. Therefore, the aims of this study were: (1) investigate the accumulation of potassium, calcium, copper, iron and zinc in the seed coat and embryo of beans seeds; (2) examine the occurrence of maternal effect in the expression levels of potassium and copper in common bean seeds; (3) to estimate heritability and gain by selection for potassium and copper contents in early generations. Thus, the seed coats of two cultivars BRS Expedito and Carioca were separated from the embryo and minerals were determined in each fraction. Also, crosses were made between IAPAR 44 x Guapo Brilhante and BRS Expedito x BRS Valente, to study the genetics of potassium, and between IAPAR 44 x IAPAR 31 and Diamante Negro x TPS Bonito, to study copper amount. In the embryo was concentrated more than 80% of potassium, 64% copper and 68% zinc and the tegument has accumulated more than 94% of calcium and 51.06% to 60.12% of iron in the seeds of BRS Expedito and Carioca cultivars. There was no significant maternal effect on the expression levels of potassium and copper in common bean seeds. Estimates of broad sense heritability of 44.08% and 79.97%, and in the narrow sense of 33.26% and 43.05% were obtained for potassium content in IAPAR 44 x Guapo Brilhante and BRS Expedito x BRS Valente crossing, respectively. For copper content was observed estimates of heritability in the broad sense of 71.90% and 79.65%, and in the narrow sense of 51.98% and 61.99% for IAPAR 44 x IAPAR 31 and Diamante Negro x TPS Bonito crossing, respectively. The increase in potassium content, for breeding, may be difficult due to the significant effect of the environment variance. For copper content, it was possible an increased of 46.78% for breeding.